Inhalation of diesel exhaust and allergen alters human bronchial epithelium DNA methylation - Clifford, Rachel L.; Jones, Meaghan J.; MacIsaac, Julia L.; McEwen, Lisa M.; Goodman, Sarah J.; Mostafavi, Sara; Kobor, Michael S.; Carlsten, Chris (Elsevier, 2017)
Background